Rosmarinus officinalis essential oil: A review of its phytochemistry, anti-inflammatory activity, and mechanisms of action involved - Borges, Raphaelle Sousa; Ortiz, Brenda Lorena Sánchez; Pereira, Arlindo César Matias; Keita, Hady; Carvalho, José Carlos Tavares (Journal of ethnopharmacology, 2019)
Plant species Rosmarinus officinalis L. (Lamiaceae; Synonyms: Salvia rosmarinus Schleid. and Rosmarinus angustifolius Mill.) is a herb widely used worldwide. In local and traditional medicine, its used for inflammation-related diseases. Currently, studies report anti-inflammatory activity in its essential oil (EORO). However, to better understand EORO’s anti-inflammatory activity its necessary to understand its phytochemistry and the signaling pathways affected by it. Hence, this review aimed to describe EORO phytochemical profile, ethnopharmacological uses, some biological activities of EORO will be described but emphasizing its anti-inflammatory potential and possible mechanisms of action involved. The research was performed using the databases Medline, Embase, BVS Regional Portal, Science Direct, CAPES Journals, and Scopus; using the keywords “Rosmarinus officinalis”, “anti-inflammatory” and “essential oil”. Additional information was gathered from related textbooks, reviews, and documents. Until now about 150 chemical compounds were identified in EORO samples, more frequently reported molecules were 1,8-cineole, α-pinene, and camphor. Studies suggest that the anti-inflammatory activity of EORO occur mainly through inhibition of NF-κB transcription and suppression of arachidonic acid cascade. Its antioxidant activity also aids by preventing injury caused by the reactive species of inflammation; its smooth muscle relaxant activity contributes to ameliorating airway inflammatory diseases. Lastly, toxicity assessments indicate low toxicity to EORO. Current evidence indicates anti-inflammatory activity in EORO, supporting its ethnopharmacological uses in inflammatory-related diseases, and potential future applications. However, although considerable acute inflammatory models were tested, more chronic inflammatory models are needed; clinical studies are still absent, this may be due to the high doses needed for essential oils to exert pharmacological effects, but recent studies show this issue can be bypassed using the oil formulated as nanoemulsions to improve its bioavailability. [Display omitted]